US based NGOs in International Development Cooperation: Survival of the Fittest? - Peter Nunnenkamp; Hannes Öhler; Tillmann Schwörer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
The non-distribution constraint of non-governmental organizations (NGOs) would be harder, and financiers as well as recipients could expect more charitable output from them, if less efficient NGOs were squeezed out of international development cooperation. We employ Probit and complementary log-log estimations to analyze which factors determine the probability of 'market' exit for almost 900 US based NGOs with overseas aid activities during the 1984-2003 period. Apart from their size and experience, we consider administrative overheads as an important aspect of NGO efficiency. We also account for other dimensions of NGO heterogeneity, including the importance of official refinancing. We find that larger administrative overheads increase the probability of exit for secular NGOs, though not for religious NGOs. Furthermore, we detect complex non-linear effects once the interactions between administrative overheads and official refinancing are taken into account.
Keywords: L31; F35; 330; non-governmental organizations; foreign aid; NGO characteristics; market exit; Probit models; complementary log-log